Efficient gene replacement by CRISPR/Cas‐mediated homologous recombination in the model diatom Thalassiosira pseudonana. Issue 1 (8th December 2022) - Belshaw, Nigel; Grouneva, Irina; Aram, Lior; Gal, Assaf; Hopes, Amanda; Mock, Thomas
Summary: CRISPR/Cas enables targeted genome editing in many different plant and algal species including the model diatom Thalassiosira pseudonana . However, efficient gene targeting by homologous recombination (HR) to date is only reported for photosynthetic organisms in their haploid life‐cycle phase. Here, a CRISPR/Cas construct, assembled using Golden Gate cloning, enabled highly efficient HR in a diploid photosynthetic organism. Homologous recombination was induced in T. pseudonana using sequence‐specific CRISPR/Cas, paired with a dsDNA donor matrix, generating substitution of the silacidin, nitrate reductase and urease genes by a resistance cassette (FCP: NAT ). Up to c . 85% of NAT‐resistant T. pseudonana colonies screened positive for HR by nested PCR. Precise integration of FCP: NAT at each locus was confirmed using an inverse PCR approach. The knockout of the nitrate reductase and urease genes impacted growth on nitrate and urea, respectively, while the knockout of the silacidin gene in T. pseudonana caused a significant increase in cell size, confirming the role of this gene for cell‐size regulation in centric diatoms. Highly efficient gene targeting by HR makes T. pseudonana as genetically tractable as Nannochloropsis and Physcomitrella, hence rapidly advancing functional diatom biology, bionanotechnology and biotechnological applications targeted on harnessing the metabolic potential of diatoms.